STUDI KELENGKAPAN PENGISIAN PERSETUJUAN TINDAKAN MEDIKDI RUMAH SAKIT UMUM AJIBARANG KABUPATEN BANYUMAS - Yuris Tri Naili; Tri Sumarni (Universitas Muhammadiyah Semarang, 2014)
Medical treatment approval is an absolute requirement to do medical treatment. According toSubekti, an agreement also called an approval because both party is agree to do something. Itcan be said that both terms (agreement and approval) have a same meaning. (Subekti, 1987,Law Agreement, Intermassa, Jakarta). Medical treatment approval form is a law agreement,therefore medical treatment approval must meet the legitimate of an agreement, as regulated inarticle 1320 and 1321 KUHP. The purpose of this research is to describe the compatibility andcompleteness of approval form fulfilment. This research conducted in Ajibarang Hospital usingdescriptive research methodology to give a detail, systematic and comprehensive description about everything related to the compatibility and completeness of approval form fulfilment.This research found that in substance the Medical Treatment Approval Form of Ajibarang Hospital has not fulfil the principle of agreement which is regulated in article 1320 and 1321KUHP, and the Medical Treatment Approval Form of Ajibarang Hospital 98% is not filledcompletely. The incompleteness is consist of : 91, 7 % the approver identity is unallocatedcompletely; 36, 7 % the patient identity is unallocated completely; 10,8% the medical recordnumber is unallocated completely; 24,8% the approver status is unallocated completely; 21,6%the signature witness of patient family is unallocated completely; 4% approver signature isunallocated completely, and 1,8 % medical treatment explanation is unallocated completely.Key word : Medical treatment approval, compatibility, completeness